Simultaneous Quantitative Determination of Four Kinds of Parabens in Soy Sauce by UPLC-MS/MS - Zhang, Jun-Xian; Miao, Ming-Ming; Niu, Xue-Mei; Li, Jin-Zhu; Han, Yi; Zhang, Ke-Qin; Zhang, Cheng-Ming (Asian Journal of Chemistry, 2014)
A new method for simultaneous determination and quantitation of four kinds of parabens (methyl paraben, ethyl paraben, propyl paraben and butyl paraben) in soy sauce has been developed by using solid-phase extraction (SPE) combined with ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Two sample type (blended and brewed) were used for method evaluation. Recoveries were mostly higher than 90 %, method detection limits ranged from 0.55 to 2.08 ng mL-1 and method quantification limits were included between 1.84-6.92 ng mL-1. Due to matrix effect, quantitation was performed by referring to a matrix matched calibration curve, for each soy sauce typology. This method was also applied to commercial soy sauce samples, with good results.